Family history of myocardial infarction as an independent risk factor for coronary heart disease. Issue 4 (April 1985) - Friedlander, Y; Kark, J D; Stein, Y
Abstract : The hypothesis that a family history of heart attack before the age of 60 years is an independent risk factor for coronary heart disease was examined in a random sample of 1044 men aged 40-70. Data on personal and family history, smoking, weight, height, plasma lipid and lipoprotein concentrations, blood pressure, and resting and exercise electrocardiograms were collected according to the standard Lipid Research Clinics protocol. A history of heart attack in first degree relatives was ascertained by interviewing the participants. Evidence of coronary heart disease was found in 123 men (reported heart attack in 20, electrocardiographic findings of ischaemic heart disease at rest in 40, and electrocardiographic findings during heart rate limited exercise in 63). Subjects with coronary heart disease had considerably higher concentrations of total cholesterol, higher blood pressures, and lower concentrations of high density lipoprotein cholesterol than those without. Twenty nine per cent of the subjects with coronary heart disease reported a history of heart attack in a first degree relative before 60 years of age compared with 19% of those without. In a multivariate logistic model, the coefficients for age, cholesterol concentrations, and hypertension were all positive and statistically significant. The coefficient for HDL cholesterol concentration was negative and significant. A family history of heart attack showed a significant positive association, indicating a relation with coronary heart disease that is independent of the other variables in the model. The relation persisted in apparently asymptomatic patients with coronary heart disease.